Nursing care of a 44-year-old man with ankylosing spondylitis staying at home - Ryś, Bogusława; Oziębała, Oliwia; Bąk, Ewelina (Journal of Education, Health and Sport, 2024)
The subject of the work is to demonstrate the importance and presentation of the course of substantive nursing care for a 44-year-old patient who has been suffering from ankylosing spondylitis for years. The first part of the work contains the medical definition of the disease of the spine joints, the etiology of the disease, familiarization with the symptoms, diagnosis and description of treatment. The second one covers the description and analysis of a specific case. The entire work presents nursing problems that patients may experience and how to prepare a nursing order card.